Wspomnienie o lekarzu, właścicielu biblioteki w Częstochowie - Tadeusiewicz, Hanna (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The article recalled the occasion of the 155 birth anniversary and the 95 death anniversary of the doctor that passed in 2012, scholar and social activist – Władysław Biegański (1857-1917), who was meritorious also for the history of books and libraries in Poland.